2016
DOI: 10.2147/oaem.s69973
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-related emergency department use: current perspectives

Abstract: Asthma is one of the most common chronic pediatric diseases. Patients with asthma often present to the emergency department for treatment for acute exacerbations. These patients may not have a primary care physician or primary care home, and thus are seeking care in the emergency department. Asthma care in the emergency department is multifaceted to treat asthma patients appropriately and provide quality care. National and international guidelines exist to help drive clinical care. Electronic and paper-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 74 publications
(95 reference statements)
0
20
0
Order By: Relevance
“…None of the patients were uninsured. It would also be relevant to note that the existing literature on ED utilization in the insured population has found race and severity to be significant predictors of recurrent ED visits [ 1 , 2 , 3 ]. This study did not find asthma severity and other socioeconomic factors like race and insurance to be significant predictors of “repeat” ED visits, suggesting that future research may be needed to understand key drivers of “repeat” ED visits and unscheduled healthcare use for childhood asthma in a largely insured population with access to primary and specialty care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the patients were uninsured. It would also be relevant to note that the existing literature on ED utilization in the insured population has found race and severity to be significant predictors of recurrent ED visits [ 1 , 2 , 3 ]. This study did not find asthma severity and other socioeconomic factors like race and insurance to be significant predictors of “repeat” ED visits, suggesting that future research may be needed to understand key drivers of “repeat” ED visits and unscheduled healthcare use for childhood asthma in a largely insured population with access to primary and specialty care.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature has found the biggest determinants of ED utilization for childhood asthma to be access to care, disease severity, and socioeconomic factors. However, the vast majority of these studies have been undertaken among uninsured children and children with insurance coverage gaps [ 1 , 2 , 3 , 12 , 13 , 14 ]. The population of interest to this study is an insured population with access to primary and specialty outpatient care for childhood asthma.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Black children are at higher risk for asthma than white children, only among those from families with a low income to federal poverty level ratio [15]. Utilization of hospital-based emergency services for the treatment of asthma, including return to the emergency department (ED) after discharge, is a significant burden to the healthcare system [16] and a negative marker for quality of care [17,18] that can also be associated with patients' social context [19,20]. In the present study, we examine an association of revisitation to the ED by children discharged with asthma with respect to their race/ethnicity combined with type of health insurance coverage.…”
Section: Introductionmentioning
confidence: 99%